MINING INDUSTRY IN CROATIA - Slavko Vujec (Rudarsko-geološko-naftni Zbornik, 1996)
The trends of World and European mine industry is presented with introductory short review. The mining industry is very important in economy of Croatia, because of cover most of needed petroleum and natural gas quantity, total construction raw materials and industrial non-metallic raw minerals. Detail quantitative presentation of mineral raw material production is compared with pre-war situation. The value of annual production is represented for each raw mineral (the paper is published in Croatian).